2012
DOI: 10.3892/mmr.2015.3418
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of enoyl coenzyme A hydratase 1 expression in colorectal cancer cells using small interfering RNA inhibits cell proliferation and migration

Abstract: Abstract. Colorectal cancer is one of the most commonly diagnosed types of cancer and is a leading cause of cancer-associated mortality worldwide. Short chain enoyl coenzyme A hydratase 1 (ECHS1) is an important gene involved in the mitochondrial fatty acid β-oxidation pathway. In addition, ECHS1 has been implicated in a variety of cancers, including breast, prostate, colon and liver cancer. The aim of the present study was to examine the expression of ECHS1 in the human HCT-8 colorectal cancer cell line. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Notably, both MFAE and MBO pathways possess ECHS1 (Figures 3 and 4). Studies involving the knockdown of ECHS1 have shown that this gene is involved in cancer cell survival, cell proliferation and metastasis 22,23 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, both MFAE and MBO pathways possess ECHS1 (Figures 3 and 4). Studies involving the knockdown of ECHS1 have shown that this gene is involved in cancer cell survival, cell proliferation and metastasis 22,23 …”
Section: Resultsmentioning
confidence: 99%
“…Studies involving the knockdown of ECHS1 have shown that this gene is involved in cancer cell survival, cell proliferation and metastasis. 22,23…”
Section: Remodelin Reduces Fatty Acid Accumulation Through Mitochondrial Fatty Acid Elongation (Mfae) and Beta Oxidation Pathwaysmentioning
confidence: 99%
“…ECHS1 is a key enzyme that catalyzes the second step of the β-oxidation pathway in fatty-acid metabolism. Apart from its critical roles in regulating fatty acid metabolism, numerous literatures have indicated that ECHS1 might be involved in the development of tumor, including colon [ 14 , 15 ], liver [ 27 ], gastric [ 17 ], and renal [ 28 ] cancer. In CRC cell lines, it has been reported that ECHS1 is able to suppress proliferation and migration through PI3K–Akt–GSKβ signaling pathways [ 15 ], and the knockdown of ECHS1 attenuates HCC proliferation by impairing cell metabolism and inducing cell apoptosis and autophagy by activating the AMP protein kinase (AMPK) pathway [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from its critical roles in regulating fatty acid metabolism, numerous literatures have indicated that ECHS1 might be involved in the development of tumor, including colon [ 14 , 15 ], liver [ 27 ], gastric [ 17 ], and renal [ 28 ] cancer. In CRC cell lines, it has been reported that ECHS1 is able to suppress proliferation and migration through PI3K–Akt–GSKβ signaling pathways [ 15 ], and the knockdown of ECHS1 attenuates HCC proliferation by impairing cell metabolism and inducing cell apoptosis and autophagy by activating the AMP protein kinase (AMPK) pathway [ 16 ]. Additionally, in the human gastric cancer cell lines, the protein levels of ECHS1 were significantly higher than those in nonneoplastic gastric epithelial mucosa cells [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation